The Retention Pond Role in Shaping Thermal Comfort and the Effect of Ventilation at Universitas Katolik Musi Charitas, Palembang, Indonesia - Dhita Wahyu Anggraeni; Abdul Rachmad Zahrial Amin; Melinda Amalia Tanjung; Intan Mustika Pasya (Journal of Artificial Intelligence in Architecture, 2026)
A retention pond is a body of water that collects water, particularly rainwater. In Palembang, there are 46 retention ponds scattered in various locations. One of them is located between Ida Bayumi University (IBA) and Musi Charitas Catholic University, situated approximately 10 meters away from the Aloysius Building. This is a factor affecting comfort because of the water content in the air carried by the wind into the Aloysius building through the window facing the pond. This research aims to determine the extent of the influence of the IBA retention pond on natural ventilation and humidity in the Aloysius Building, through the window as the entry and exit of air. The method employed is a descriptive quantitative approach, utilizing Computational Fluid Dynamics (CFD) simulation and the Hobometer tool to measure wind speed and humidity within the building.  The results of the analysis obtained wind speeds of 0-2.5 meters per second and turbulence effects in several rooms. The comfort standard based on Ashrea-55 shows that it is warm with an average RH of 67.6% and a temperature of 28.9°C. To achieve optimal comfort, the corridor space requires large ventilation so that the maximum wind flow can reach the spaces on the left and right of the building, especially on the second and third floors.